Implementation of Education Digitalization Policy in the ERA of the Covid-19 Pandemic (Case Study at the Department of Education and Culture Manado City, North Sulawesi Province) - Lady Grace Jane Giroth; Harol R. Lumapow; Tellma M. Tiwa; Viktory Nicodemus Joufree Rotty (Researchparks Publishing, 2022)
This study aims to analyze the implementation, model and evaluation of education digitization policies in the era of the covid-19 pandemic (Case Study at the Education and Culture Office of Manado City, North Sulawesi Province). This research was conducted with a qualitative method. This research is a qualitative descriptive research with a case study approach. Primary data collection was conducted by interview. In addition, supporting data is secondary data from documents, articles or news related to the policy of digitizing education in the era of the covid-19 pandemic. The data analysis technique used is data reduction, data presentation and conclusion drawing. Based on the analysis carried out, the results obtained are that the implementation of the education digitalization policy in the era of the covid-19 pandemic has been carried out well, but to maximize its implementation, collaboration between school principals, teachers, school commissions and school supervisors, parents and students is needed. The model for implementing the education digitization policy used is a top-down model. While the evaluation of the implementation of the education digitization policy is the need for guidance and information provision from the Regional Government in this case the Manado City Education and Culture Office and the leadership role of the school principal greatly determines the success of the implementation of digitalization of education policies in every school. parents as well as students. The model for implementing the education digitization policy used is a top-down model. While the evaluation of the implementation of the education digitization policy is the need for guidance and information provision from the Regional Government in this case the Manado City Education and Culture Office and the leadership role of the school principal greatly determines the success of the implementation of digitalization of education policies in every school. parents as well as students